The syntax of information-structural agreement - Mursell, Johannes (Linguistik aktuell ;, 2021)
"In this research monograph, Johannes Mursell discusses the syntactic impact of information-structural features on agreement. So far, the syntactic contribution of this type of feature has mostly been reduced to movement of topics or foci clause-initial position. Here, the author looks at a different phenomenon, syntactic agreement, and how this process can be dependent on information-structural properties. Based partly on original fieldwork from a typologically diverse set of languages, including Tagalog, Swahili, and Lavukaleve, it is argued that for most areas for which information-structural features have been discussed, it is possible to find cases where these features influence phi-feature agreement. The analysis is then extended to cases of Association with Focus, which does not involve phi-features but can still be accounted for with agreement of information-structural features. The book achieves two main goals: first it provides a uniform analysis for different constructions in unrelated languages. Second, it also gives a new argument that information-structural features should be treated as genuine syntactic features"--